2012
DOI: 10.1021/jp306315r
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen and Oxygen Evolution Photocatalysts Synthesized from Strontium Titanate by Controlled Doping and Their Performance in Two-Step Overall Water Splitting under Visible Light

Abstract: A visible-light-induced two-step overall water splitting was achieved by combining two types of photocatalysts prepared by introducing foreign elements into the identical mother structure with a controlled electronic band structure. Strontium titanate (SrTiO 3 ) was selected as the mother structure and was doped with either vanadium (and sodium) or rhodium to introduce visible light sensitivity. By utilizing these two types of SrTiO 3 -based photocatalysts, simultaneous liberation of hydrogen (H 2 ) and oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 26 publications
2
44
0
Order By: Relevance
“…Konda et al reported the existence of two different doped Rh species as mentioned above is responsible for this spectral pattern [23]. The absorption with a peak occurring at ~600 nm ) and O 2p orbitals to form the VB, resulting in a negative-potential shift of the VB top, which we confirmed in our previous study [19]. After depositing either Pt or Ru onto Cr,Ta-TiO 2 or Rh-SrTiO 3 , respectively, the absorption over a wider wavelength region (>400 nm) clearly increased, indicating the successful deposition of Pt or Ru.…”
Section: Figures 3(a)-3(d)supporting
confidence: 89%
See 1 more Smart Citation
“…Konda et al reported the existence of two different doped Rh species as mentioned above is responsible for this spectral pattern [23]. The absorption with a peak occurring at ~600 nm ) and O 2p orbitals to form the VB, resulting in a negative-potential shift of the VB top, which we confirmed in our previous study [19]. After depositing either Pt or Ru onto Cr,Ta-TiO 2 or Rh-SrTiO 3 , respectively, the absorption over a wider wavelength region (>400 nm) clearly increased, indicating the successful deposition of Pt or Ru.…”
Section: Figures 3(a)-3(d)supporting
confidence: 89%
“…We repeatedly deaerated this system to a final pressure of 2.5 Pa and then introduced argon gas into the system in the same way. For these reasons, we considered that the detection of N 2 originated from the intruded air from outside, and the effect of residual O 2 (and N 2 ) in water was possibly excluded [19] …”
Section: Photocatalytic Water-splitting Testsmentioning
confidence: 99%
“…The apparent quantum yield decreases with increasing incident light wavelength. This indicates that the water-splitting reaction over the samples is associated with the DRS absorption spectra [44]. Compared with other typical TiO2/SrTiO3 nanostructures with different morphologies [26,[30][31][32][33][34], the H-TiO2/SrTiO3 heterostructured porous microspheres present much higher photocatalytic activity.…”
Section: Resultsmentioning
confidence: 87%
“…Nevertheless, "metal-semiconductor" heterojunctions mostly provide photoactivation under light irradiation with wavelengths shorter than 400 nm. Amongst recently-developed "metal-semiconductor" heterojunctions with a narrow band gap and band edges suitable for water photosplitting, Pt/PbBi 2 Nb 2 O 9 [42], (V,Rh)/SrTiO 3 [43], (Zn,Rh,Cr)/Ga 2 O 3 [41], (La,Rh,Au)/SrTiO 3 [44], Au/CeO 2 [45], (Mo,Au)/BiVO 4 [46], sulfide-based materials [22], CoO [47] and cadmium chalcogenides [48] have to be noted.…”
Section: Metal-semiconductor Heterojunctionsmentioning
confidence: 99%